Synthesis and Evaluation of Some New Isatin Hydrazones for Their Antibacterial, Antioxidant and Cytotoxic Activities - Venkateshwar Rao, J.; Sarangapani, M. (Asian Journal of Chemistry, 2010)
Twenty new isatin-3-[N2-(N,N-dialkylamino/diphenylamino/ heterylamino)acetyl]hydrazones IV(a-t) were synthesized from five different isatin-3-[N2-(chloroacetyl)]hydrazones III(a-e) by reacting with dimethyl amine, diethylamine, N-methylpiperazine, morpholine and diphenylamine in presence of anhydrous potassium carbonate and dry acetone. The intermediates were obtained from isatin hydrazones on condensation with chloroacetyl chloride. The title compounds were characterized by their spectral data and evaluated for in vitro antibacterial, antioxidant and cytotoxic activities. Some of the compounds showed promising biological activity against B. subtilis and S. aureus.